Evaluation of strategies by the Brazilian Ministry of Health to stimulate the municipal response to AIDS Avaliação de estratégias do Ministério da Saúde para incentivar a resposta municipal a AIDS no Brasil - Alexandre Grangeiro; Maria Mercedes Loureiro Escuder; Euclides Ayres de Castilho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to evaluate strategies by the Brazilian Ministry of Health to expand the municipal response to AIDS. Cities "included" and "not included" in Federal strategies for "municipalization" of the response were compared according to the response profile and trends in the epidemic. Multinomial logistic regression was used, among other statistical procedures. Municipalities included from 1994 to 1998 showed higher chances of providing HIV diagnostic testing [OR = 15.0; 95%CI: 5.6-40.1], of having AIDS services [OR = 18.4; 95%CI: 8.4-40.5], and reducing cases involving heterosexual [OR = 3.1; 95%CI: 1.4-7.3], homosexual/bisexual [OR = 3.0; 95%CI: 1.4-6.2], and IDU transmission [OR = 6.6; 95%CI: 2.9-14.9] as compared to those "included in 2003" and "not included". There were no associations between the included Municipalities, greater coverage in prevention, the reduction in cases due to vertical transmission or blood transfusion, or mortality rates. Municipalities with a more structured response were associated with better results. The findings suggest that the municipalization policy contributed to improvement in the local response to AIDS. Avaliar as estratégias do Ministério da Saúde para ampliar a resposta municipal a AIDS. Cidades "incluídas" e "não incluídas" nas estratégias federais de municipalização foram comparadas segundo perfil da resposta e da epidemia. Regressão logística multinomial foi usada, entre outros procedimentos estatísticos. Municípios incluídos entre 1994/98 apresentaram maior chance de ofertar o diagnóstico do HIV [OR = 15,0; IC95%: 5,6-40,1], possuir serviços de AIDS [OR = 18,4; IC95%: 8,4-40,5] e reduzir casos por transmissão heterossexual [OR = 3,1; IC95%: 1,4-7,3], homo/bissexual [OR = 3,0; IC95%: 1,4-6,2] e uso de drogas injetáveis [OR = 6,6; IC95%: 2,9-14,9] do que os "incluídos em 2003" e os "não incluídos". Não houve associações entre municípios incluídos, a maior cobertura de prevenção e a redução de casos por transmissão vertical, transfusão de sangue e taxas de mortalidade. Municípios com resposta mais estruturada associam-se a melhores resultados. Os achados sugerem que a política de municipalização contribuiu para aprimorar a resposta.